Electrocardiographic changes after high-dose corticosteroid pulse therapy in pemphigus patients. (17th November 2018) - Pishgahi, Mehdi; Dadkhahfar, Sahar; Robati, Reza M.; Kheradmand, Zohreh; Shahidi-Dadras, Mohammad; Zargari, Omid; Elpern, David J.
Abstract: Purpose: The objective of the current study was to evaluate the effect of intravenous methylprednisolone pulse therapy on myocardial repolarization alterations, especially QT dispersion in anticipation of cardiovascular risks in patients with pemphigus vulgaris. Methods: The current study is a prospective-controlled study on the electrocardiographic changes after methylprednisolone pulse therapy in 50 patients with pemphigus vulgaris. Results: A total of 50 patients (28 female and 22 male) were included in our study. The mean heart rate was significantly higher in male patients both before (92 ± 10.80 versus 82.75 ± 12.01 ms) and after pulse therapy (102.73 ± 14.26 versus 91.07 ± 15.02 ms) ( p  value < .01). The value of heart rate was significantly greater after receiving steroid pulse therapy. Corrected QT dispersion before pulse therapy was 19.92 ± 8.2 ms that increased to 40.68 ± 18.12 ms after treatment ( p  value < .001). Conclusion: Our study shows that there is a relationship between pulse steroid infusion and increased predisposition to the occurrence of cardiac arrhythmias. QT dispersion could be a good marker to assess this risk in these patients.